Analysis of performance indicators in outdoor vs. indoor professional padel - Escudero-Tena, A.; Crespo, M.; Sanchez-Alcaraz, B. J.; Munoz, D. (International Journal of Performance Analysis in Sport, 2023)
The aim of this research was to analyse the differences in performance indicators between outdoor and indoor professional padel tournaments according to the gender of the players, the round in the draw, the set number, and their result. Performance indicators (winning break points, errors, winning shots, winning smashes…) of 942 sets (402 matches) from the 2022 World Padel Tour (WPT) season were collected from WPT TV open access videos. Differences between outdoor and indoor tournaments in performance indicators according to the analysed variables were analysed through descriptive and inferential statistics. The results showed significant differences between outdoor and indoor tournaments in men`s padel with a higher number of winning shots (p < 0.001) in indoor matches, and in women`s padel with a higher number of smashes (p < 0.001), winning smashes (p = 0.003) and errors (p = 0.002), in outdoor matches. In addition, the rounds in the draw, the set number, and its result were found to be parameters that influence the performance indicators analysed according to the tournament (outdoor and indoor). These findings are of great interest, as they provide players and coaches with an understanding of the performance indicators that affect the style of play depending on whether the tournament is played outdoors or indoors.